Der Vorsorge-Albtraum - Carl Christian von Weizsäcker (Wirtschaftsdienst, 2013)
– Neoclassical economics assumes that provision for the future is simply a matter of the will to save enough of one's current income. However, saving requires the availability of a secure instrument. Historically, the availability of such instruments has always been a problem. The social security system of the 20th century provided a great improvement in this respect. In the meantime, life expectancy has grown to exceed retirement age by about two decades. The savings requirements for this long retirement period lead to an excess of the supply of savings (including social security contributions), which vastly exceeds the capacity of the private sector to build real capital. Government debt is required to prevent the provision nightmare.
Keywords: H6; 330; Sparen; Zeitpräferenz; Wirtschaftsordnung; Neoklassik; Kapitalmarkttheorie; Dogmengeschichte